Managing Diabetes - Vora, Jiten; Evans, Marc.; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2012)
Managing Diabetes is a up-to-date, comprehensive showcase of the current pharmaceutical trends in treating diabetes and provides a unbiased, inclusive discussion of current and emerging treatments by well-known experts in the field.
Introduction -- Management strategies for diabetes -- Insulin therapies -- Non-insulin agents for diabetes -- New and future therapies -- Managing the complications of diabetes.
Keywords: Medicine; Family medicine; Diabetes; Endocrinology; Metabolic diseases; Medicine & Public Health; Diabetes; Endocrinology; General Practice / Family Medicine; Metabolic Diseases